Assessing Protectionism and Subsidies in Agriculture : A Gravity Approach - Paiva, Claudio (IMF Working Papers; Working Paper ;, 2005)
This paper provides the first comprehensive empirical analysis of agricultural trade using a gravity model. The data set covers bilateral trade in agricultural goods for 152 countries over the periods 1990-93 and 1999-2002. The estimations support claims that protectionism and distortive subsidies to agriculture remain widespread in more developed nations, which are shown to import less and export more agricultural products than expected given other economic, political, and geographic determinants of trade. However, some developing regions that are often thought to be the main victims of industrial-country protectionism are also found to be relatively closed to agricultural trade.